ESRA19-0107 Are our patients satisfied with the care received with the ERAS (enhanced recovery after surgery) protocol in elective colorectal surgery?. (30th August 2019) - Cabellos, M; Muñoz, R; Labalde, M; Torralba, M; Rodriguez Fraile, JR; Atance Martínez, JC
Abstract : Background and aims: The aim of this study was to know patient´s satisfaction after the implementation of an ERAS protocol in elective colorectal surgery (EQRS). It is based in the RICA (Intensive Recovery in Abdominal Surgery) program published in 2014 by the Ministry of Health, Social Services and Qquality of Spain. Methods: Inclusion criteria: ECRS, ≥18 years, appropriate cognitive state and ASA I-II-III. Exclusion criteria: urgent surgery and higher concomitant surgical processes. Four days after hospital discharge, a telephone survey was carried out based on the RICA clinical survey. It was performed on the first 119 patients who underwent ECRS according to an ERAS protocol. Results: The mean compliance of the protocol was 72.5%. 112 (94.2%) patients were very satisfied with care and treatment received by the health staff, 6 (5%) quite satisfied, and 1 (0.8%) dissatisfied. 118 patients (99.2%) would be reoperated according to this protocol. Most of them considered that the information given by surgeons (94 [79%]) and anesthethics (99 [83.2%]) was very good, and they valued the pre-anesthesia consultation as one of the most positive aspects of the protocol. 80 (67%) did not have nausea and vomiting in the postoperative period. 94 (77.69%) patients rated their pain during hospital admission as ≤3 with the Visual Analogue Scale (VAS). Conclusions: Most of the patients operated on ECRS according to an ERAS protocol were very satisfied or satisfied with the assistance received. Standardized surveys are needed to compare results